Complaints filed in the medical ethics court of Antioquia against doctors, why are they sanctioned? - Manuela Vélez-Gaviria; Tatiana Andrea Zapata-Correa; Luis Fernando Botero-Posada; Rocío Gómez-Gallego; Diana Marcela Marín-Pineda (Iatreia, 2023)
Background: there are few studies about the complaints presented against physicians, limiting feedback and education, aspects that tend to improve health services and quality of care. Objective: to characterize the complaints against physicians and their consequences. Antioquia. 2008-2013. Methods: cross-sectional descriptive study. All complaints filed with the Medical Ethics Court of Antioquia, 2008-2013, which had a ruling in the second half of 2018, were reviewed. Characteristics of the personnel involved, event that motivated the complaint, violated regulations and sanction were evaluated Results: among 679 doctors involved, 461 complaints were found, 43.4% of them general practitioners. The main reason for filing a complaint was the poor care received by patients (20.9%), and the main rule by which processes were opened was Law 23 Article 15, which speaks about informed consent (17.3%); being also the most sanctioned (16.2%). Most of doctors involved (58.6%) had the processes archived because the court did not find a basis for the complaint; however, 23 (3.4%) were sanctioned, with suspension from the practice of medicine in 60.8%. Of the remaining, 17.4% had public censorship, 13% private reprimand and 8.7% private written censor-ship or public verbal censorship. Conclusions: the omission or poor completion of the informed consent constitutes the main reason for sanction; however, the real trigger that leads to filing a complaint is the perception of poor attention. Continuous ethical education in professional practice is fundamental in reducing law-suits for malpractice.